Investigation of Thrombotic Tendency in Hypertensive Urgencies: Thrombotic Tendency in Hypertensive Urgencies - Sahin, Taner; Günay, Nurullah (Chronicles of Precision Medical Researchers, 2022)
Aim: Hypertension is a significant risk factor for the development of thrombotic events. Mean platelet volume is a marker that correlates closely with platelet activity in uncontrolled hypertension. In this study, we aimed to monitor changes in MPV and other laboratory parameters during a 2-hour follow-up in patients diagnosed with hypertensive urgency and who were administered captopril or amlodipine treatment. Materials and Method: In this study, a total of 100 patients who were considered to have hypertensive urgency in the ED were separated into two groups in a randomized controlled manner. To reduce their blood pressure, 25 mg captopril tablets were orally given to fifty patients and 5 mg amlodipine tablets were orally given to fifty patients. MPV and other laboratory parameters were recorded at 0 minutes, 60 minutes, and 120 minutes. Results: There was no difference between the two groups in terms of the patients’ first MPV values (p > 0.05). MPV was increased after 60 minutes in the captopril group. However, despite the evidence of a decrease at the end of 120 minutes, the difference was not found (p > 0.05). MPV was decreased in the amlodipine group at the end of 60 and 120 minutes, but no difference was found (p > 0.05). Conclusion: In this study, the decrease in MPV values caused by amlodipine was more remarkable than that caused by captopril. We believe that for patients who present with hypertensive urgency, MPV values should be reduced in the early period for the prevention of thrombosis.